Colloidal and rheological behavior of aqueous dispersions of buriti tree (mauritia flexuosa) gum - da Silva, Diego Aires; Santos, Pedro Henrique; Pena, Rosinelson da Silva (Emirates Journal of Food and Agriculture, 2017)
The temperature, concentration and pH variables influence the aqueous dispersion of the gum properties. In this context, the aims of this research were to characterize the gum obtained from the buriti tree (Mauritia Flexuosa) trunk exudate, as well as to evaluate the colloidal and rheological behavior of the aqueous dispersions of this gum. Thus, the centesimal composition, absolute zeta (ζ) potential as a function of pH (1.2 to 4.0), particle size distribution, as well as the rheological properties of the gum at different temperatures (15, 20, 25, 30, and 40 °C) and concentrations (4, 5, 8, and 10% (m/v)) were studied. In addition, the Newton, Power Law, and Herschel-Bulkley models were fitted to the rheological data. Buriti tree gum (BG) was found to have 10.43% moisture, 5.05% ashes, 0.68% lipids, 3.09% proteins, and 80.76% carbohydrate. The aqueous dispersion of the gum (1%) had a ζ value of -17.1 mV with a tendency for greater stability at pH < 4 and polydisperse particle size distribution (45 nm to 648.1 nm diameter) with PDI (polydispersity index) of 1. The aqueous dispersion with 4 and 5% gum had typical Newtonian fluid behavior and became pseudoplastic at concentrations of 8 and 10%. The Herschel-Bulkley model had the best fit to the rheological data (r2 > 0.99). Gum dispersion viscosity decreased with higher temperature and lower concentration. The activation energy (Ea) value for gum dispersion ranged from 9.07 to 17.35 kJ/mol.